Entrepreneurial Orientation and Entrepreneurial Intention among Youth Corp Members in North East Nigeria: The Role Of Perceive Access to Finance - Abdullahi, Abubakar Sadiq (2017)
Entrepreneurial intention (EI) is one of the major contributing factors to the formation, growth and development of entrepreneurship. Nigeria is making all possible effort in encouraging youths for self reliance especially youths in the North east region where violence has erupted for many years and destroyed the flow of economic activities.The current study therefore examined the moderating role of perceived access to finance (PAF) in the relationship between entrepreneurship orientation (EO) and entrepreneurial intention (EI).We employed questionnaires adapted from past studies to collect data from a sample of 354 corps members residing in the North east Nigeria.The results of the partial least squares structural equation modeling (PLS-SEM) showed a significant positive relationship between entrepreneurship orientation and entrepreneurial intention.Our results also revealed that perceived access to finance significantly moderates the relationship between entrepreneurship orientation and entrepreneurial intention.The study therefore recommended that government should ensure that youth corps members are given adequate entrepreneurial orientation and finance to improve their intention for entrepreneurship.Our review of past empirical studies on the relationship between entrepreneurship orientation and entrepreneurial intention showed inconsistencies.To fill this gap and add to the exiting body of knowledge, the current study integrated a third variable as a moderator of the relationship.